2023
DOI: 10.1109/ojvt.2023.3265363
|View full text |Cite
|
Sign up to set email alerts
|

Cybersecurity of Autonomous Vehicles: A Systematic Literature Review of Adversarial Attacks and Defense Models

Abstract: Autonomous driving (AD) has developed tremendously in parallel with the ongoing development and improvement of deep learning (DL) technology. However, the uptake of artificial intelligence (AI) in AD as the core enabling technology raises serious cybersecurity issues. An enhanced attack surface has been spurred on by the rising digitization of vehicles and the integration of AI features. The performance of the autonomous vehicle (AV)-based applications is constrained by the DL models' susceptibility to adversa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 210 publications
0
2
0
Order By: Relevance
“…These studies highlight the importance of tailored risk assessment frameworks to address the unique challenges of ATs. Frameworks leveraging driving simulators [19], trajectory planning [20], liability considerations [21], and cybersecurity [22] illustrate the diverse application and critical nature of comprehensive risk assessments. Collectively, this body of work highlights the need for interdisciplinary approaches to ensure the safe integration of ATs into the transportation ecosystem.…”
Section: Deployment Risk Assessmentsmentioning
confidence: 99%
“…These studies highlight the importance of tailored risk assessment frameworks to address the unique challenges of ATs. Frameworks leveraging driving simulators [19], trajectory planning [20], liability considerations [21], and cybersecurity [22] illustrate the diverse application and critical nature of comprehensive risk assessments. Collectively, this body of work highlights the need for interdisciplinary approaches to ensure the safe integration of ATs into the transportation ecosystem.…”
Section: Deployment Risk Assessmentsmentioning
confidence: 99%
“…Similarly, Zhang et al (2021) [63] extended the Unified Theory of Technology Acceptance and Use model and found that risk expectation and consumer innovativeness are influential factors in the acceptance of autonomous vehicles. The development of autonomous vehicles has been facilitated by advances in artificial intelligence (AI) and machine learning (ML) technologies [66][67][68]. The cybersecurity of autonomous vehicles has also been a matter of debate.…”
Section: Literature Review Research Model and Hypothesesmentioning
confidence: 99%
“…Then, we remove the predictions of the injected points from the predicted label set and calculate the accuracy. This can be mathematically expressed as Equation (10).…”
Section: Robustness Evaluation Metricsmentioning
confidence: 99%
“…The susceptibility of DL networks to adversarial attacks raises concerns regarding their use in safety-critical applications like AVs, as the security of AVs is correlated with the DL networks those AVs employ. As a result, adversarial attacks against AVs have attracted a lot of attention, and numerous studies were conducted to examine the adversarial vulnerabilities of AVs and defend against them [10,11].…”
Section: Introductionmentioning
confidence: 99%